2018
DOI: 10.2478/romneu-2018-0048
|View full text |Cite
|
Sign up to set email alerts
|

A descriptive study of cranio-cerebral injuries admitted in tertiary care center of coastal Andhra Pradesh

Abstract: Introduction: Demographic and clinical profile of traumatic brain injury (TBI) of a particular place is very crucial for strengthening the guidelines. The details of same are scant from a tertiary institute, Nellore district. The present study aims to explore the demographic, injury and clinical aspects of cerebro-cranial injury patients from an institute setup. Methods: The study consists of two years retrospective data and one year prospective data. The study was approved by institute ethical committee. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 10 publications
1
4
0
Order By: Relevance
“…The current study was conducted on dead cases due to traumatic causes in Soad Kafafy Hospital. As regards the age of cases, most cases (85.7 %) were below 40 years, whereas the lowest number were more than 40 years (14.3 %) of all cases, this was in line with research from India (Sivakumar et al, 2018) and studies from England, Belgium and South Africa, that revealed that young individuals in active age groups had the highest risk of traumatic injuries (Jasper, 2014). The study's findings may be the consequence of young adults as young adults often engage in riskier activities compared to other age groups, such as extreme sports, reckless driving, or participating in dangerous stunts, which increases their chances of experiencing traumatic injuries (El-Farouny, 2021).…”
Section: Discussionsupporting
confidence: 89%
“…The current study was conducted on dead cases due to traumatic causes in Soad Kafafy Hospital. As regards the age of cases, most cases (85.7 %) were below 40 years, whereas the lowest number were more than 40 years (14.3 %) of all cases, this was in line with research from India (Sivakumar et al, 2018) and studies from England, Belgium and South Africa, that revealed that young individuals in active age groups had the highest risk of traumatic injuries (Jasper, 2014). The study's findings may be the consequence of young adults as young adults often engage in riskier activities compared to other age groups, such as extreme sports, reckless driving, or participating in dangerous stunts, which increases their chances of experiencing traumatic injuries (El-Farouny, 2021).…”
Section: Discussionsupporting
confidence: 89%
“…Two-wheelers, whether motorised or non-motorised are the most common type of vehicle in LMICs as they are the cheaper and more widely available form of transportation in these countries [15]. Other epidemiological studies from India and Pakistan also show that RTCs occur more often in this group of road users, with the most common injury being TBIs [16][17][18][19][20]. The vulnerability to RTCs with a greater risk of sustaining a TBI arises because they are generally less protected than four-wheeler occupants where the current infrastructure, especially in LMICs, tends to prioritise cars and other motorised four-wheelers [21].…”
Section: Discussionmentioning
confidence: 99%
“…Majority of the head and spine injury patients (around two-thirds) in our study were middle-aged earning members of the family, which is similar to other studies. 1,3 Less than 5% of patients were under 10 years of age. Males were four times more commonly involved in injuries compared with females.…”
Section: Neurotrauma Auditmentioning
confidence: 99%
“…Mode of injury was found to be similar to those reported in other studies found in the literature. 1,3,6 Few cases of trauma due to animal attack were also encountered in regions with dense forest areas in the vicinity. Around 25 and 18% of head and spine injury patients, respectively, were under alcohol influence at the time of injury, suggesting a need for strict implications of traffic rules as well as awareness in general population.…”
Section: Neurotrauma Auditmentioning
confidence: 99%
See 1 more Smart Citation